Suppression of pancreatic ductal adenocarcinoma growth by intratumoral delivery of attenuated Salmonella typhimurium using a dual fluorescent live tracking system - Zhou, Sujin (Cancer Biol Ther, 2016)
Pancreatic ductal adenocarcinoma (PDAC) has the poorest prognosis among all malignancies and is resistant to almost all current therapies. Attenuated Salmonella typhimurium strain VNP20009 has been deployed as powerful anticancer agent in a variety of animal cancer models, and previous phase 1 clinical trials have proven its safety profiles. However, thus far, little is known about its effect on PDAC. Here, we established CFPAC-1 cell lines expressing an mKate2 protein and thus emitting far-red fluorescence in the subsequent xenograft implant. VNP20009 strain was further engineered to carry a luciferase cDNA, which catalyzes the light-emitting reaction to allow the observation of salmonella distribution and accumulation within tumor with live imaging. Using such VNP20009 strain and intratumoral delivery, we could reduce the growth of pancreatic cancer by inducing apoptosis and severe necrosis in a dosage dependent manner. Consistent with this finding, intratumoral delivery of VNP20009 also increase caspase-3 activity and the expression of Bax protein. In summary, we revealed that VNP20009 is a promising bacterial agent for the treatment of PDAC, and that we have established a dual fluorescent imaging system as a valuable tool for noninvasive live imaging of solid tumor and engineered bacterial drug.